The relationship between LGBT executives and firms' value and financial performance - Isabel Costa Lourenço; Donatella di Marco; Manuel Castelo Branco; Ana Isabel Lopes; Raquel Wille Sarquis; Mark T. Soliman (Journal of Risk and Financial Management, 2021)
Drawing on resource-based theory, we analyze the relationship between having LGBT executives in a firm's leadership positions and its value and financial performance. The existence of LGBT executives is considered to be associated with employee and customer goodwill towards LGBT-friendly policies and practices and to lead to human capital and reputational benefits. Our findings suggest that there is a positive effect of the presence of LBGT executives on a firm's value, both directly and indirectly, through its effect on the firm's financial performance. We interpret this as suggesting that besides the direct effect of the existence of LGBT executives on a firm's value, an indirect effect also exists, mediated through financial performance, presumably through the effect that this has on employee and customer goodwill towards LGBT-friendly policies and practices. As far as we are aware, our study is the first to examine the impacts of the presence of LGBT executives, as well as distinguish between its direct and indirect effects on firm value.
Keywords: 330; financial performance; LGBT; market value; resource-based theory; sexual orientation and identity; simultaneous equations